2013
DOI: 10.1007/s00281-013-0391-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of the aryl hydrocarbon receptor (AhR) in lung inflammation

Abstract: Millions of individuals worldwide are afflicted with acute and chronic respiratory diseases, causing temporary and permanent disabilities and even death. Oftentimes, these diseases occur as a result of altered immune responses. The aryl hydrocarbon receptor (AhR), a ligand-activated transcription factor, acts as a regulator of mucosal barrier function and may influence immune responsiveness in the lungs through changes in gene expression, cell-cell adhesion, mucin production, and cytokine expression. This revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
76
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 121 publications
1
76
0
Order By: Relevance
“…Important genes include AHR, CD69, FAS, and JUN (Table 4). AHR (arylhydrocarbon receptor) plays an important role in airway inflammation via its effect on bronchial epithelia and immune cells (23). After ligation, the AHR-dioxin complex induces the transcription of detoxification enzymes to detoxify dioxin-like compounds into physiologic metabolites and influence immune responsiveness and mucosal barrier function of epithelium in the lung.…”
Section: Resultsmentioning
confidence: 99%
“…Important genes include AHR, CD69, FAS, and JUN (Table 4). AHR (arylhydrocarbon receptor) plays an important role in airway inflammation via its effect on bronchial epithelia and immune cells (23). After ligation, the AHR-dioxin complex induces the transcription of detoxification enzymes to detoxify dioxin-like compounds into physiologic metabolites and influence immune responsiveness and mucosal barrier function of epithelium in the lung.…”
Section: Resultsmentioning
confidence: 99%
“…10,39,40 In these models, AhR activation led to reduced eosinophilia, inhibited Th2 and challenged with OVA as described, and total and OVA-specific IgE and IgG1 was measured in serum as described. 31 (a) Total IgE,…”
Section: Discussionmentioning
confidence: 99%
“…cytokine and IgE production, increased Th1 cytokine levels, and decreased expression of the Th2 transcription factor GATA3. 10,39,40 However, these studies did not investigate whether the AhR ligands were acting directly on T cells or on accessory cells that may programme the T-cell responses. Our lymph node antigen recall experiments showed that T-cell activation in AhR À/À lymph node cells was significantly stronger than was seen in controls, with greater antigen-specific proliferation and cytokine production (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations